Antihyperglycemic and analgesic activity studies with boiled Cicer arietinum L. seeds - Md Najmul Hossain, Mithila Saha, Shahnaz Rahman, Sanjida Haque, Rownak Jahan, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2015)
In oral glucose tolerance tests, methanol extract of boiled seeds of Cicer arietinum (MECA) significantly and dose-dependently reduced blood glucose levels in glucose-loaded mice by 27.7, 31.9, 36.2, and 42.2%, respectively, at doses of 50, 100, 200 and 400 mg per kg in comparison to a standard antihyperglycemic drug, glibenclamide, which reduced blood glucose levels by 48.2% at a dose of 10 mg per kg. In acetic acid induced writhing tests in mice, MECA at the afore-mentioned doses reduced the number of writhings, respectively, by 21.4, 35.7, 39.3, and 46.4% versus the 42.9 and 53.6% reductions observed with a standard analgesic drug, aspirin, at doses of 200 and 400 mg per kg, respectively. MECA thus demonstrated considerable antihyperglycemic and analgesic properties and may be used to alleviate high blood glucose levels and provide relief from pain.
Keywords: Antihyperglycemic, Cicer arietinum, analgesic, Fabaceae.